Al-Ghazali's Thoughts on Language and Education: Their Relevance for Contemporary Arabic Language Teaching - Muhammad Fajar Maulana; Kamal Yusuf; Sabki Ati Murtafi'ah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study examines Al-Ghazali’s thought on language and education and explores its relevance within contemporary Arabic language pedagogy. Departing from the tendency to position Al-Ghazali merely as a moral authority, this research situates his ideas within a broader epistemological framework that integrates language, ethics, and cognition. The study aims to critically reinterpret Al-Ghazali’s concepts and assess their potential contribution to addressing the limitations of instrumentalist approaches in modern language teaching. This research employs a qualitative-descriptive method with a conceptual and philosophical approach, relying on library research. Primary sources include Al-Ghazali’s major works, while secondary sources consist of contemporary studies in linguistics and language pedagogy. Data are analyzed through interpretive and critical analysis to identify key concepts and their possible contextual transformation. The findings reveal that Al-Ghazali’s perspective on language emphasizes ethical intentionality (niyyah), disciplined speech (adab al-kalām), and the inseparability of knowledge and moral formation. These principles offer a critical lens to evaluate contemporary Arabic language teaching, which often prioritizes communicative efficiency over interpretive depth and ethical awareness. However, the study also finds that Al-Ghazali’s framework cannot be directly applied to modern educational contexts due to differences in historical, epistemological, and institutional settings. This study concludes that Al-Ghazali’s thought is best understood as a reflective and critical resource rather than a prescriptive pedagogical model. Its relevance lies in enriching the epistemological foundation of language education, particularly by reintroducing ethical and reflective dimensions into language learning. Nevertheless, any attempt to integrate these ideas requires careful reinterpretation and adaptation to ensure compatibility with contemporary educational demands.